Globalization and inflation dynamics: The impact of increased competition - Argia M. Sbordone (Federal Reserve Bank of New York, 2008)
This paper analyzes the potential effect of global market competition on inflation dynamics. It does so through the lens of the Calvo model of staggered price setting, which implies that inflation depends on expected future inflation and a measure of marginal costs. I modify the assumption of a constant elasticity of demand, standard in this model, to provide a channel through which an increase in the number of traded goods may affect the degree of strategic complementarity in price setting and hence alter the dynamic response of inflation to marginal costs. I first discuss the behavior of the variables that drive the impact of trade openness on this response, and then I evaluate whether an increase in the variety of traded goods of the magnitude observed in the United States in the 1990s might have a significant quantitative impact. I find that it is difficult to argue that such an increase in trade would have generated a sufficiently large increase in U.S. market competition to reduce the slope of the inflation-marginal cost relation.
Keywords: E31; 330; Inflation dynamics; globalization; Globalisierung; Internationaler Wettbewerb; Außenhandelspreis; Import; Inflationsrate; New-Keynesian Phillips Curve; USA